An Error Analysis in Using Personal Pronouns at Tenth Grade Student - Mawar Putri, Ithalia; Nur Agustina, Hiqma; Sudarmaji, Imam (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
This research aims to analyze students’ error in using personal pronouns in writing descriptive text at the tenth grade students of SMA Negeri 14 Kabupaten Tangerang. The method of this research is descriptive analysis which is the writer analyze the errors made by students then classify the types of errors into four types as: omission, addition, misformation and misordering, after that calculated the students’ error using percentages formula. The result of the research findings shows errors in omission, addition, misformation and misordering. From the result of this research, it can be concluded that misformation is the most frequent error with of error made by students in using personal pronouns in writing descriptive text.